An Efficient and Practical Chemoenzymatic Route to (3R,3aR,6R,6aR)-Hexahydrofuro[3,2-b]furan-6-amino-3-ol (6-Aminoisomannide) from Renewable Sources - Zullo, Valerio; Petri, Antonella; Iuliano, Anna (SynOpen, 2021)
The synthesis of 6-aminoisomannide is easily achieved starting from the renewable, inexpensive, and commercially available isosorbide in 66% overall yield. A biocatalyzed highly regioselective acetylation of the 3-endo hydroxyl group of isosorbide was followed by the stereospecific interconversion of the 6-exo hydroxyl group into an azido group, through reaction with trifluoromethanesulfonic anhydride, followed by nucleophilic displacement of the triflate group by sodium azide. Finally, reduction of the azido group and deacetylation of the 3-hydroxy group were performed in one pot using LiAlH4.
Keywords: isomannide; isosorbide; chiral amino alcohols; supported enzyme; lipase